Meningkatkan Motivasi Belajar Al-Quran pada Anak Melalui Metode Tahsin - Shohibul Ardhi; Samsul Hakim; Sudirman; Masyhur Aziz; Muhammad Taufiq Hidayatullah; Muhammad Ridho Maghfiroh; Muhammad Hamzani; Muhammad Iqbal; Muhammad Su’eb; Makruf; Najmi; Hulaemi; Aidi; Muhammad Al Khudori; Nining Sri Fahroyati (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
Teaching and learning activities are conducted for elementary (SD/MI) In Gelogor, Subdistrict Kediri, West Lombok Regency. At this educational level, the motivation to learn the Quran among children is minimal due to their limited ability to read the Quran. The main objective of these instructional activities is to enhance the learning motivation of children, enabling them to become proficient in reading the Quran. The teaching method employed is descriptive, utilizing a combination of lectures, discussions, question-and-answer sessions, and simulations. The outcomes of the teaching and learning sessions are as follows: Firstly, students achieve a better understanding of the theory of Quranic recitation. Secondly, they exhibit an improved motivation to learn the Quran. Thirdly, through the tahsin method, students find it easier to enhance or refine their Quranic reading skills. Fourthly, there are noteworthy changes observed after the implementation of the tahsin method